Evidence for underuse and overuse of antidepressants in older adults: results of a large population-based study - Böhlen, Friederike; Freigofas, Julia; Herzog, Wolfgang; Meid, Andreas; Saum, Kai-Uwe; Schöttker, Ben; Brenner, Hermann; Haefeli, Walter E.; Wild, Beate (International journal of geriatric psychiatry, 2019)
Objectives: Depression is common among elderly people. However, diagnosis and adequate treatment is frequently difficult. Research on underuse and overuse of antidepressants in elderly persons is scarce. This study investigates the utilization and appropriateness of pharmacological and psychological depression treatment in a large cohort of community-dwelling adults. Methods: A subsample of 3117 participants (aged 55-85 y) of the third follow-up (2008-2010) of the large population-based German ESTHER study was included. Depression was assessed using the eight-item Patient Health Questionnaire (PHQ-8). In the course of a home visit, study doctors collected complete information on medication. Logistic regression analyses were conducted to determine the relationship of depression with both underuse and overuse of antidepressants. The analyses were then adjusted for socioeconomic variables, psychosomatic comorbidities, and motivation to seek help. Results: One hundred sixty-three participants (5.2%; 95% confidence interval [CI], 4.5-6.1) fulfilled the criteria for major depression. Underuse of antidepressants was present in 126 depressed participants (77.3%; 70.1-83.5). Persons who were motivated to seek help, who had an established depression diagnosis, or who were taking more than five different medications had lower odds of underuse. Anxiety was associated with higher odds for underuse. Overuse of antidepressants (prescription without clinical indication) was found in 96 cases (41.7%; 35.3-48.4) of all antidepressant prescriptions. Conclusions: Depression treatment in older adults is frequently insufficient; it appears to depend on diagnosis as well as the patients' motivation to seek help. Education regarding the diagnosis of depression in the elderly as well as guidelines for appropriate treatment is needed.
Gesehen am 04.04.2019